TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENGHINAAN DI MEDIA SOSIAL MENURUT PASAL 27 AYAT 3 UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (STUDI KASUS BEBERAPA PUTUSAN PENGADILAN) - Alya Oktari Rahma; Mukhlis R; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The development of science and technology, including telecommunications, media andinformatics (telematics) globally, has had an impact on changing the mindset and perspective ofthe community in carrying out all activities that are oriented towards aspects of ease and speed inexchanging access to information. Technological advances are developing rapidly, enabling theemergence of new types of crimes that can be committed through social media. In the current erathat is very closely related to social media, the most common legal problems that occur aredefamation in the form of insults in cyberspace. The purpose of this thesis research is, firstly, tofind out the juridical review of several court decisions on perpetrators of insults on social media.Second, find out the judge's interpretation of the sentence imposed on the perpetrator of the crimeof defamation on social media based on the Joint Decree regarding the ITE Law.The type of research used in this thesis research is normative research. This study useddata consisting of primary legal materials, secondary legal materials, tertiary legal materials anddata collection techniques were carried out using the library study method. In this study also usedqualitative data analysis to produce descriptive data.From this research, there are two things that can be concluded that first, in relation toinsult the special rules are regulated in Law No. 19/2016 concerning Amendments to Law No.11/2008 concerning ITE. Article 27 Paragraph (3) is considered a "rubber article". The reason forbeing labeled as a rubber article is because this article does not have clear benchmarks and canthreaten freedom of expression, especially civil society and the press. If you look at the attachmentto the SKB that has been listed, a government official cannot use Article 27 Paragraph (3) as aform of legal protection if a performance or policy he publishes draws criticism, opinion orjudgment from the public if the policy he makes is deemed inappropriate with a sense of justice insociety. Second, the case that the author analyzes from a positive legal perspective in the case thatthe decision handed down by the court is not in accordance with what has been stipulated by lawcontained in Article 27 Paragraph (3) of the ITE Law No 19/2016 which is basically better , it'sjust that there is no guarantee of legal certainty regarding insult or defamation.Keywords: Criminal Act of Insult, Social Media, ITE Law.